Understanding Differences In Emotional Experiences Among Caregivers In Caring For Children Under Five Exposed To HIV - Hayati, Happy; Wanda, Dessie; Nurhaeni, Nani; Nuraidah, Nuraidah (Indonesian Journal of Global Health Research, 2024)
An increase in HIV cases in housewives is at risk of increasing the population of children exposed to HIV. Caregivers of children exposed to HIV are at risk of having problems caring for children exposed to HIV. The difficulties experienced by caregivers can be affected by the condition of the child, who may or may not be infected with HIV. This study aims to get an n overview of the emotional experience of caregivers in caring for children underfive who are exposed to HIV. Methods: The research design uses a qualitative method with a phenomenology approach. Data collection was carried out using snowball sampling techniques and obtained from ten participants domiciled in Jakarta and its surroundings. The participants recruited in this study are caregiver of HIV-exposed children. Data collection was carried out using in-depth interview techniques. Data analysis uses thematic analysis using the Colaizzi method. This study obtained ten participants consisting of seven biological mothers, two children’s relatives and one foster parent. There were seven children with HIV-negative and five children with HIV-positive. Two caregivers in this study cared for more than one child exposed to HIV, namely one child with HIV-positive and one child with HIV-negative. The study found three themes: easy versus complex; grace and entrustment; and love and pity. This study concluded the that there are differences in emotional experiences among caregivers in caring for children underfive exposed to HIV influenced by the child’s HIV status. Positive affirmations and emotional support from health professionals adjusted to the values and socio-cultural condition of caregivers will benefit caregivers in providing adequate care for children.